Assessing the Clinical Utility of the Question, "Is Your Child/Are You Back to Normal?" in Pediatric Concussion Symptom Resolution. (February 2018) - Vollmer, Brandi L.; Kirkwood, Michael W.; Comstock, R. Dawn; Currie, Dustin; Grubenhoff, Joseph A.
This study investigates the relationship between the general question, "Is your child/are you back to normal?" and a validated postconcussive symptom scale when assessing symptom resolution following concussion. Children with acute concussion were enrolled during an emergency department visit. Sensitivity and specificity analyses compared the true/false question, "My child is/I am back to normal" at 3 days postinjury with the Concussion Symptom Inventory (CSI; gold standard). A total of 201 participants were enrolled in the study with complete data. The true/false questions of "My child is/I am back to normal" had sensitivities of 78.4% and 59.3% and specificities of 75.0% and 86.4% for caregiver and child responses, respectively, when compared with their corresponding CSI. This study demonstrates that asking a parent or child if the child is back to normal has poor sensitivity and modest specificity in determining if a child's symptoms have resolved within 3 days of sustaining a concussion relative to a standardized symptom scale.